If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y = -2 + -1x Solving 6y = -2 + -1x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '6'. y = -0.3333333333 + -0.1666666667x Simplifying y = -0.3333333333 + -0.1666666667x
| (x*40)+(1.5x*5)=576 | | 69*200000/X=17.92 | | 5/7m35 | | -8(s+2)=28 | | x*40+1.5*x*5=30000 | | 9w=10w-4 | | 2y-63.0=10.0 | | 2b-7/3=3/3 | | x-2.0=27.0 | | -8x+6-12=-30 | | 6x+21=x+7 | | 12+4x-x=x+28 | | 5x+28.0=58.0 | | 2b-31/3=11/3 | | (x+5)=(3x-2) | | 11/30x360 | | 7x^2+8xy+y^2=45 | | (5v-9)(8-v)=0 | | ((12v^6)-(14v^3))/(2v^3) | | 2mx^2+3mx=0 | | 2(4x-3)=58 | | 2(x-2)+3x=6x+7-(x-3) | | 15x-220=5x-10 | | 16-11x+12=-16x | | -2x-7+3x=2(5x-9) | | 3e/(e^x) | | 159*200000/X=8.50 | | 2-55m-5=73 | | 32x+48=11-x-7 | | 2(3x-5)=2x-1 | | (2n+6)(4n+2)+16=80 | | 2n^2-40=-11n |